Author Correction: Pulmonary adiaspiromycosis in armadillos killed by motor vehicle collisions in Brazil - Pedro Enrique Navas‑Suárez (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.